Magneto-Rayleigh-Taylor instability in compressible Z-pinch liner plasmas - 杨学 肖德龙 丁宁 刘杰 (Chinese physics B, 2017)
In this paper, the characteristics of magneto-Rayleigh-Taylor（MRT） instability of liner plasmas in Mag LIF is theoretically investigated. A three-region slab model, based on ideal MHD equations, is used to derive the dispersion relation of MRT instability. The effect of compressibility on the development of MRT instability is specially examined. It is shown that the growth rate of MRT instability in compressible condition is generally lower than that in incompressible condition in the presence of magnetic field. In the case of zero magnetic field, the growth rate in compressible assumption is approximately the same as that in incompressible assumption. Generally, MRT instability in（x, y） plane can be remarkably mitigated due to the presence of magnetic field especially for short-wavelength perturbations. Perturbations may be nearly completely mitigated when the magnetic field is increased to over 1000 T during liner implosions. The feedthrough of MRT instability in liner outer surface on inner surface is also discussed.